COMPARATIVE LEGAL ANALYSIS OF THE DEVELOPMENT OF LEGISLATION ON COUNTERING CYBERBULLYING AMONG SCHOOL-AGE CHILDREN IN MODERN JURISDICTIONS - Nukusheva Айгуль Ашимовна; Kuandykov Бахытжан Журсунович; Zhailau Жанат (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article is devoted to the prevention and counteraction of such a modern phenomenon as cyberbullying among school-age children, the search for measures to prevent and combat it. The study substantiates the conditions conducive to the transformation of traditional bullying into a virtual one. Cyberbullying is often interpreted as an electronic form of traditional bowling, which is accompanied by features of virtual communication: anonymity, lack of empathy, uncontrollability and prolonged storage of traumatic information. To solve this problem, psychological factors are highlighted, and emphasis is also placed on the need for legal regulation of countering cyberbullying, in particular, establishing responsibility. To effectively solve this problem, it is extremely important to actively highlight and consolidate the concepts of bullying and cyberbullying at the legislative level. Specifically, it is necessary to adopt a law aimed at combating cyberbullying in the school environment, including measures of responsibility for children, parents and, if necessary, teachers. It is also important to establish competent authorities that will monitor cases of cyberbullying, analyze the most common methods and interact with Internet service providers for joint efforts to eliminate this problem. The results obtained serve as the basis for formulating recommendations on improving legislative approaches to combating cyberbullying in modern society. As a necessary measure, it is proposed to establish such responsibility not for children, but for parents, and in some cases for teachers. It is necessary to introduce new institutions, develop cultural values among school students, focusing on preventing cyberbullying. It is pointed out that there is a need for appropriate development of juvenile justice, because for older students with a well-formed psyche, who, due to their age, can already bear legal responsibility, it is necessary to establish a certain punishment. At the same time, the focus of attention does not necessarily focus on administrative and criminal liability measures, it is important to concentrate efforts on preventive and educational measures.